Assessment concerns - Mc Donald, Betty (Caribbean Examinations Council (CXC), 2000)
After laying the foundation by distinguishing between testing and assessment, and exploring some non-traditional forms of assessment, this paper seeks to consolidate key issues by delineating features of non-traditional forms of assessment. Positioning assessment in its sociological perspective, the paper attempts to identify developmental, symbol-system, multiple faculties of intelligences, multivariate dimensions, individual differences, creativity, group/team work, time, work-based, problem-based, performance-based, and computer-based dimensions, that adversely affect the formulation of suitable modes of assessment, both at the classroom level and at the national and international level.
Inaugural Conference of Caribbean Examination Bodies: Global Trends in Educational Assessment: Challenges and Opportunities for the Caribbean, Barbados, March 22-24, 2000